Determination of trace Elements in Hematite’s Iron Reference Material JSS-804-1 using ko-INAA (Geologica Macedonica, 2013)
Different trace elements in hematite’s iron ore reference material (JSS-804-1) were investigated using k0-instrumental neutron activation analysis (k0-INAA). To avoid the interference of iron as matrix elements, а method for its separation was applied. Namely, a liquid-liquid extraction procedure by diisopropyl ether (DIPE) in hydrochloric acid solution and determination of trace elements in the aqueous phase was undertaken. The k0-INAA method was applied to determine the content of the investigated elements thus making it possible to follow the distribution of 39 elements (with intermediate/medium and long half-lived radionuclides) in the studied referent material. An important advantage of the proposed method is the possibility to determine the content of several trace elements after Fe separation. Additionally, the elimination of the matrix element also lowered the detection limit for some trace elements compared to their corresponding values determined by k0-INAA and certified values for some elements.